Analisis Risiko Keselamatan dan Kesehatan Kerja pada Produksi Tiang Pancang Pracetak dengan Metode HIRARC - Chalsi Mala Sari; Mochamad Gaharu Dida Devedo; Johannes E. Simangunsong; Lidwina Putri Astani; Ananda Ion Jahfal; Muhammad Ibadurrahman Arrasyid Supriyanto (Jurnal Talenta Sipil, 2026)
The precast concrete industry involves the use of reinforcement-processing machinery, prestressing systems, batching plants, overhead cranes, heavy equipment, and lifting and material-handling activities that may pose occupational accident risks. This study aims to identify hazards, assess risk levels, and formulate risk-control recommendations for the precast pile production process at PT X, Kutai Kartanegara. A qualitative descriptive approach was employed using the Hazard Identification, Risk Assessment, and Risk Control (HIRARC) method. Data were collected through field observations, documentation, and interviews with four respondents selected through purposive sampling, consisting of one section head, one operator, and two workers. Risk levels were determined by combining the likelihood of occurrence and the severity of consequences using a scale of 1–5. The study identified 65 potential risks, comprising 15 risks associated with material and equipment inspection, 6 risks related to reinforcement work, 9 risks arising from mould preparation and reinforcement installation, 22 risks associated with concrete casting and curing, and 13 risks related to mould dismantling, quality control, and product storage. The assessment results classified 40 risks as low, 14 as moderate, 6 as high, and 5 as extreme. The extreme risks were primarily associated with the snapping or recoil of PC strands, workers being struck by concrete buckets or precast piles, the manual installation of lifting hooks, and the movement of cranes, excavators, and stacked products. The recommended priority controls include reducing hazardous manual activities, establishing exclusion zones and safety barriers, installing crane guide rails and warning alarms, developing lifting standard operating procedures, providing blind-spot awareness training, installing safety signage, and ensuring the appropriate use of personal protective equipment.